A PREPARATION OF DRAMA PERFORMANCE BY CREATING VISUAL SYMBOL RESPONSE AMID THE COVID-19 PANDEMIC - Munikahi Purba; Rita Inderawati (HISKI, 2021)
This study aimed to elaborate on the students’ creativity in responding to literary works, in this case, a poem entitled Beowulf by utilizing visual symbols. The population of this research students from the 4th semester of English education in Sriwijaya University in the academic year 2020/2021 consists of 73 students. The researcher used the purposive sampling method. There were 34 students chosen as samples. The instruments of the research were test and documentation of their Visual Symbol Response which were analyzed by using Rubric for Creativity. The result showed students can appreciate literature using visual symbols. These symbols can help students visualize the words written in literary works so as to form an interesting performance. On the other hand, the students have been able to elaborate on critical thinking and also their creativity. The students were generally not at the degree of